Atividade antiangiogênica da forma recombinante da proteína 21 de Trypanosoma cruzi - Teixeira, Samuel Cota (2016)
Chagas disease, caused by the parasite Trypanosoma cruzi, is the cause of Chronic chagasic cardiomyopathy (CCC). The prospection of innovative therapeutic agents against CCC is a major task. The recombinant form of 21 (rP21), a secreted T. cruzi protein involved in host cell invasion and on progression of chronic inflammatory processes have been studied as a potential novel therapeutic target. Our present work aimed to verify and investigate the impact of rP21 in the formation of blood vessels in vitro and in vivo. First, tEnd cells were treated with different concentrations of rP21 or bacterial extract and viability and cellular adhesion were evaluated by MTT and angiogenesis inhibition by Matrigel tube formation assay and murine model. To verify the proteolytic activity of rP21 on extracellular matrix (ECM) components, fibrinogen, matrigel and fibronectin was incubated with rP21 or not. In addition, we performed proliferation assays and cell cycle analysis. Furthermore, the accumulation and distribution of F-actin was determined by Phalloidin staining using ImageJ software. Finally, tEnd cells were incubated with rP21 and the mRNA levels were analyzed by real-time PCR. Our results showed that rP21 did not alter cell viability and adhesion, but strongly inhibited vessel formation in vitro and in vivo. Tube formation assay showed that angiogenesis inhibition was dependent of the CXCR4-rP21 binding. In addition to these results, we observed that the rP21 was able to inhibit cell proliferation and promoted a significant reduction in the number of 4n cells (G2/M phase). Moreover, we found that rP21 significantly increased F-actin levels and this protein was able to modulate expression of genes related to angiogenesis and actin cytoskeleton. However, rP21 showed no significant activity on the matrix components. In this sense, we conclude that the rP21-endothelial cells (ECs) interaction via CXCR4 promotes inhibition of vessel formation through a cascade of intracellular events, such as inhibition of ECs proliferation and modulation of the expression of molecules associated with angiogenic processes and actin cytoskeleton.